A Simple Model of An International Lender of Last Resort - Huang, Haizhou; Goodhart, C... (Washington, D.C. : International Monetary Fund, 2000)
This paper develops a simple model of an international lender of last resort (ILOLR). The world economy consists of many open economies, each with a banking system and a central bank operating under a pegged exchange rate regime. The fragility of the banking system and the limited ability of a domestic central bank to provide international liquidity together can cause currency and banking crises. An international interbank market can help an economy with the needed international liquidity, but with potential costs of international financial contagion. An ILOLR can play a useful role in providing international liquidity and reducing international contagion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banks and Their Policies; Monetary Policy, Central Banking, and the Supply of Money and Credit